Tendencias teóricas de dos propuestas de pedagogía de la memoria en la educación superior colombiana (2019)
Two models of university teaching of the pedagogy of memory in Colombia are studied: one developed at the National Pedagogical University (Bogotá) and another implemented at the De La Salle University (Bogotá). Based on the bibliographic supports published in each university, the article carefully observes the two proposals. Precisely, the academic-university contexts in which the pedagogy of memory is promoted are identified; then, the basic theoretical affiliations and their central concepts. The article shows a fundamental constant, typical of the anamnetic-narrative horizon in education: thanks to the use of memory and narration, university education opens a pedagogical path capable of critically integrating university education and social reality, the academic reading of the reality and the life experience of students, in order to promote the construction of civic coexistence in Colombia.